Kalıpyargılar ve Sosyal Yargı / The Streotype and The Social Judgement - Işıtan, İbrahim (Journal of History Culture and Art Research, 2016)
The Streotype and The Social Judgement Abstract The concept of stereotype, an important topics of social psychology is closely related to prejudice and discrimination. Stereotypes may drag people into generalization and failure in judgements in addition to many unwanted behavioral outcomes. The first section of the article deals with the definition of the concept of stereotype and ascertains the motives of individuals who intend acting in accordance with stereotypes, followed by offering various solutions to this very problem. The second section points out the effect of stereotypes on interpretation of the social judgement and the social cognition while the third section dwells on how stereotypes can be changed. This study, which presents a summary of the researches about the stereotype and the social judgement is of importance in terms of indicating how stereotypes turn into prejudices and how they eventually cause discrimination. Kalıpyargılar ve Sosyal Yargı Öz Kalıpyargı sosyal psikolojinin önemli konularından biridir. Kalıpyargı kavramı önyargı ve ayrımcılık kavramlarını da anımsatmaktadır. Kalıpyargı, davranış planında birçok istenmeyen sonuçlarıyla, kişileri yargıda genelleme ve hata yapmaya sürükleyebilmektedir. Makalenin birinci bölümü, kalıpyargı kavramının tanımı konusunu ele almakta, kişilerin kalıplaşmış inançlarla hareket etmeyi tasarlamalarının hangi sebeplere dayandığını ortaya koymakta ve çeşitli tedbir yolları önermektedir. İkinci bölümde, kalıpyargıların sosyal yargıları ve bilgileri yorumlama üzerine etkisine dikkat çekilmektedir. Üçüncü bölümde ise, kalıpyargıların nasıl değiştirilebileceği konusu üzerine durulmaktadır. Kalıpyargı ve sosyal yargı konusunda yapılan araştırmaların bir özeti şeklinde sunulan bu çalışma, kalıpyargıların önyargıya nasıl dönüştüğünü ve sonuç itibariyle ayrımcılığa nasıl yol açtığını göstermesi bakımından önem arz eder.